Maximizing Throughput at Soft Airfields - Mouton, Christopher A. (RAND Corporation, 2013)
Because soft airfields can support only a limited number of takeoffs and landings, it is important to understand how to maximize the cargo throughput at these soft fields. This report shows that there is an optimum landing weight that allows for maximum cargo delivery. This optimum landing weight is constant and independent of both aircraft ramp weight and the ability of the soil to resist compressive loads.